Making sense of groups in organizations: A historical review - Silva, M. Gabriela (Proceedings of the 15th Conference of the International Academy of Management and Business (IAMB), 2013)
Groups have been a vital element of organizational life for a long time. At the level of the formal organization, groups are constituted through purely technical criteria (e.g., the division of labour) to accomplish meaningful ends in a coordinated fashion. It is well documented, for example, that groups are an integral part of the competitive advantage for many companies. Similarly, the use of team-based organizations, a management fad popular during the 1980s, continues to be practised even after the publicity boom had ebbed. In each of these cases, group-based work structures become broadly accepted as important, relevant, and necessary at improving effectiveness. In conjunction with these formal (also labelled work) groups, there are a number of informal groups in organizations. They are neither intended nor anticipated by those who deliberate create the organization. Informal groups almost always arise as a result of attempts to modify the work environment. They create adaptive activities, which are often antagonistic to the organization’s collective purpose, but are essential to allow their members to fulfil a wide range of psychological, social and personal purposes. Numerous formal groups interrelate with each other and many informal groups develop interlinks between themselves. Both informal and formal groups are also interconnected with each other. Informal groups arise out of the particular formal arrangement that exists in organizations, but informal groups can also be sufficiently powerful to affect the formal design of the organization. In the light of this, the recognition of a plurality of views and forms to study and use groups in the workplace is very helpful. However, this does not mean that groups have always desirable consequences for its members or the organization. The present study aims to re-examine the arguments and counterarguments about the value of groups by exploring key concepts about groups and the contours of the study of group behaviour from World War II onwards.